Malaysia and Indonesia of Women in Strengthening the Family for Prevention of Violent Extremism Through Tolerance and Peace Values - Alimul Muniroh; Syahidah Rena; Halim bin Ismail; Moh. Sahlul Khuluq (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
This research endeavors to examine the integral role of women in preventing violent extremism within the Lamongan district and Kuala Lumpur, Selangor, Malaysia, utilizing a Participatory Action Research (PAR) approach. Through collaborative engagement with the community, women actively participate in identifying issues, developing interventions, and collectively shaping strategies to counteract extremist ideologies. The PAR methodology ensures a bottom-up perspective, allowing women to take an active role in problem-solving and decision-making processes. The study reveals that women, particularly in Lamongan and Kuala Lumpur, are central in challenging and countering extremist narratives within their families, fostering empowerment and ownership in the process. Beyond households, women extend their influence to the broader public, imparting essential lessons on religious tolerance and the imperative of fostering peaceful coexistence. Based on these findings, it is recommended that future initiatives embrace participatory approaches, recognizing and leveraging the unique role of women in countering violent extremism, while supporting ongoing PAR initiatives to empower women and foster more harmonious and tolerant societies.